PENGARUH PREDIKTABILITAS MEREK, KESUKAAN PADA MEREK, KOMPETENSI MEREK, REPUTASI MEREK DAN KEPERCAYAAN PADA PERUSAHAAN TERHADAP LOYALITAS MEREK HONDA: ( Studi Kasus : Mahasiswa Pengguna Sepeda Motor Honda di Fakultas Ekonomi Unika Santo Thomas Medan ) - Simangunsong, Elisabeth; Sinaga, Ria Veronika; Manihuruk, Yosefa Pasca Ulina (Jurnal Manajemen dan Bisnis, 2022)
The purpose of the study was to analyze the effect of brand predictability, brand preference, brand competence, brand reputation, trust in the company on brand loyalty. The sample size was 96 respondents. Data were collected through questionnaires and documentation. The data analysis method used descriptive analysis and multiple linear regression and to test the hypothesis used t test and F test. The results showed the multiple regression equation: LM = 6.337 + .032PM + .755KPM + .119KM + .030RM + .163KPP, meaning that all observed independent variables have a positive influence on brand loyalty. The variable that has a greater influence is the brand preference variable than the other variables. With the t test there are two variables that are not significant, namely the brand predictability variable and brand reputation with t value < t table. While the other three variables, namely brand preference, brand competence and trust in the company have a significant influence on Honda brand loyalty. While the calculated F value = 51.065 > F table, this means that the variables of brand predictability, brand preference, brand competence, brand reputation and trust in the company have a significant influence simultaneously on Honda brand loyalty. The value of the correlation coefficient of brand predictability, brand preference, brand competence, brand reputation and trust in the company to brand loyalty has a strong relationship of r = 0.826. While the coefficient of determination is 0.682 which means that the variables of brand predictability, brand preference, brand competence, brand reputation and trust in the company are able to explain 68.2% of brand loyalty while 31.8% is influenced by other factors. It is advisable for PT Astra Honda Motor to increase the variables of brand preference (KPM), brand competence (KM), and trust in the company (KPP) which have a positive influence on brand loyalty. Then PT Astra Honda Motor needs to improve the variables related to brand predictability (PM) and brand reputation (RM) because they do not have a positive influence on Honda brand loyalty. Based on the correlation coefficient value of the brand predictability variable, brand preference, brand competence, brand reputation and trust in the company to brand loyalty have a strong relationship of r = 0.826. While the coefficient of determination is 0.682, which means that the variables of brand predictability, brand preference, brand competence, brand reputation and trust in the company are able to explain 68.2% of brand loyalty while 31.8% is influenced by other factors. these other factors (for example, service quality, speed of service, friendliness in service and other factors)